PENGARUH LABA AKUNTANSI DAN ARUS KAS TERHADAP RETURN SAHAM PERUSAHAAN YANG LISTING DI BEI - Sri Purwanti, Yul Chomsatu, Endang Masitoh W. (ITB AAS INDONESIA, 2015)
This study aimed to examine the effect of accounting earnings and cash flow to stock returns companies listed on the Stock Exchange . This study used a sample of 44 companies. Samples were selected based on purposive sampling technique. Data used is secondary data. Analysis of the data using the classical assumption test and multiple linear regression analysis. Variables used in this study is the accounting profit , operating cash flow , cash flow financing , and cash flows of the investment as an independent variable. Stock return as the dependent variable. The results show that accounting earnings and cash flow simultaneously significant effect on stock returns. Accounting profit significantly influence stock returns. Operating cash flow does not have a significant effect on stock returns . Financing cash flows have a significant effect on stock returns. Investment cash flow does not have a significant effect on stock returns. Keywords : Earnings, Cash, Stock Return